Association Between Long-Term Visit-to-Visit Hemoglobin A1c and Cardiovascular Risk in Type 2 Diabetes: The ACCORD Trial - Huang, Dan; Huang, Yong-Quan; Zhang, Qun-Ying; Cui, Yan; Mu, Tian-Yi; Huang, Yin (Frontiers in Cardiovascular Medicine, 2021)
Background: To explore the association between visit-to-visit variability of Glycated hemoglobin (HbA1c) and cardiovascular outcomes in type 2 diabetes patients of the Action to Control Cardiovascular Risk in Diabetes (ACCORD) study. Methods: We conducted a post-hoc analysis on the ACCORD population including 9,544 participants with type 2 diabetes mellitus. Visit- to-visit variability of HbA1c was defined as the individual standard deviation (SD), coefficient of variation (CV), variability independent of mean (VIM) across HbA1c measurements. The clinical measurements included primary outcome, total mortality, cardiovascular death (CVD), nonfatal myocardial infarction (MI) event, nonfatal stroke, total stroke, heart failure, macrovascular events, and major coronary events (CHD). Results: Over a median follow-up of 4.85 years, 594 and 268 participants experienced all-cause mortality and cardiovascular mortality, respectively. After adjusting for baseline HbA1c levels and confounding factors, the adjusted hazard (HR) comparing patients in the highest versus the lowest quartile CV of HbA1c variability was 1.61 (95% CI 1.29-2.00) for primary outcome. Similar trends for secondary outcome were also observed. There was no association between HbA1c fluctuation and nonfatal stroke. Noticeably, there was a 66% greater risk for all-cause mortality among patients in the highest versus lowest quartile (HR 1.66, 95% CI 1.27-2.17). Conclusions: Greater variability of HbA1c is associated with higher risk for cardiovascular complications and all-cause death in type 2 diabetes mellitus. Our study stresses the significance of well-controlled glycemic levels for improving cardiovascular outcomes. Further randomized clinical trials are required to confirm these findings.